Unrestricted prevalence of sedentary behaviors from early childhood - Fariba Azabdaftari; Parisa Jafarpour; Mohammad Asghari-Jafarabadi; Behjat Shokrvash; Parvin Reyhani (BMC, 2020)
Abstract Background Light and sedentary behaviors impose heavy challenges on societies. The objectives of this study are to identify child sedentary behaviors, and to examine the relationship between parent knowledge and behavioral style on children's sedentary time in Iran. Methods This cross-sectional study was done among children and their parents selected randomly using multi-stage method, from 12 urban districts in Tabriz, Iran;2017. Data were collected through designing a multi-sectional questionnaire adopted from the Bjelland and previous studies to assess the time spent on sedentary behaviors among children/adolescents along with parent knowledge and behavioral style. Results From 480 children/adolescents and their parents 54.6% came from middle class families, and 55.62% were boys aged 2 to18. The percentage of time spent more than 120 min per day (min/d) on weekdays was for watching television (TV): (girls 24.4%, boys 21.0%), for playing computer and video games: (girls 38.7%, boys 54.7%), for electronic media communication (EMC): (girls 52.8%, boys 60.2%). The associated factors for watching TV: child age [12 years and above OR = 1.37; 95% CI = 0.53-3.54], parent knowledge [OR = 0.59, 95% CI = 0.35-0.99], and communicative styles [OR = 1.43, 95%CI = 1.11-1.86], and for playing computer and EMC: child age [5 years old and above OR = 4.83,95% CI =1.52-15.38, 12 years old and above OR = 13.76, 95% CI= 4.22-24.91], family socio-economic status [middle class OR = 2.52, 95% CI = 1.54-4.11, high class OR = 5.53, 95%CI = 1.80-15.89]. Conclusion There is an urgent need to combat the unrestricted prevalence of sedentary behaviors among Iranian children/ adolescents who use computers and other electronic devices more than the recommended time every day from early childhood. Parents should be provided with appropriate information about adverse effects of using electronic devices longer than recommended time by children. It is also essential to teach them beneficial communicative styles to monitor their children's sedentary behaviors.